1999
DOI: 10.1103/physrevc.59.1298
|View full text |Cite
|
Sign up to set email alerts
|

High-spin states in doubly odd176Reand signature inversion inπh9/2

Abstract: High-spin states in doubly odd 176 Re were investigated by means of in-beam ␥-ray spectroscopy techniques using the multidetector array GASP. Excited states of 176 Re were populated using the 165 Ho( 16 O,5n) reaction at a beam energy of 101 MeV. Seven rotational bands have been observed and their configurations have been discussed. Alignments, band crossing frequencies, and electromagnetic properties have been analyzed in the framework of the cranking model. Signature inversion phenomena in the h 11/2 i 13/2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…Similar isomeric states have been observed in 176 Re[4] and 176 Ir[30]. The isomeric lifetime can be roughly estimated by using the experimental internal conversion coefficient 0.62, the theoretical internal conversion coefficient 0.27, and the time window of 200 ns: 91 ns.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…Similar isomeric states have been observed in 176 Re[4] and 176 Ir[30]. The isomeric lifetime can be roughly estimated by using the experimental internal conversion coefficient 0.62, the theoretical internal conversion coefficient 0.27, and the time window of 200 ns: 91 ns.…”
mentioning
confidence: 73%
“…These values are taken from the compilation in Refs. [4,44] and can be found in Table III. Concerning the quadrupole moment, we refer to Q 0 = 7.3 eb of the groundstate band in 172 W [45].…”
Section: The Comparison Of Experimental B(m1)/b(e2) Values With Theormentioning
confidence: 98%
See 1 more Smart Citation
“…Low-spin signature inversion has been systematically observed in deformed odd-odd nuclei throughout the chart of nuclides (see Refs. [2,[4][5][6][7][8][9][10], and references therein), related to the high-j πg 9/2 ⊗ νg 9/2 , πh 11/2 ⊗ νh 11/2 , πh 11/2 ⊗ νi 13/2 , πh 9/2 ⊗ νi 13/2 , and πi 13/2 ⊗ νi 13/2 configurations. Great theoretical efforts have been devoted to the understanding of low-spin signature inversion in deformed odd-odd nuclei.…”
Section: Introductionmentioning
confidence: 99%
“…Great theoretical efforts have been devoted to the understanding of low-spin signature inversion in deformed odd-odd nuclei. Nuclear triaxiality and protonneutron residual interaction have been proposed as possible reasons for the inversion phenomenon [2,6,7,[11][12][13][14]. Furthermore, theoretical studies have suggested that the occurrence of signature inversion is associated closely with * Electronic address: zxh@impcas.ac.cn the positions of the Fermi surfaces of nucleons [2,15] and the configurations of states [14].…”
Section: Introductionmentioning
confidence: 99%